The Reimbursement Rate of New Rural Cooperative Medical Scheme and Self-Rated Health Among Rural Middle-Aged and Elderly - Xie, Xingquan; Hu, Ying (Frontiers in Public Health, 2022)
Objectives: The ultimate goal of the New Rural Cooperative Medical Scheme (NRCMS) is to improve physical and psychological health and aim to provide equitable, affordable, cost-effective healthcare services for all rural people. One of our major concerns from the perspective of policy outcome is whether middle-aged and elderly can benefit from the insurance to improve self-rated health. The main objectives of this study are to answer the questions that the reimbursement rate of the NRCMS is a possible explanation of why and how rural middle-aged and elderly shift from non-medical service inputs to medical service to produce health based on a family production theory.Methods: Data were obtained from the China Health and Retirement Longitudinal Study (CHARLS) conducted in 2018, which involved 1030 rural adults aged 45 years and older, and ordinal logistic regression estimator and two-step regression were used to examine these assumptions. Our approach controlled for the health status of those people at the same administrative level of the hospital.Results: Our study shows some interesting results. First, the reimbursement rate of NRCMS predicted a higher level of SRH among rural middle-aged and elderly, but that all of the indirect effect of it on SRH could be explained in total by satisfaction of local medical services utilization (ab=0.0492). Second, the results further showed that the odds ratio of satisfaction from affordable, convenient, high-quality medical services is 2.402 times (p<0.01) greater for those with higher reimbursement levels than for their counterparts with lower reimbursement. Third, the odds ratios of inpatient care visit, outpatient care visit, and physical examination among policyholders of NRCMS are also 1.116, 1.628, and 1.08 times greater, respectively, than their counterparts who are not satisfied with these local medical services.Conclusions: Our results concluded that generous insurance reimbursement can reduce the price of healthcare and costs of utilization that both had a dramatic effect on SRH among middle-aged and elderly when their demand for medical treatment is incurred. The government should focus on the healthcare cost, utilization, and health benefit calculations of health insurance policy options at the stage of rapid aging in rural China.